ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LABA DAN “ARUS KAS” MASA DEPAN PADA PERUSAHAAN GO PUBLIC - Indri Yuliafitri (InFestasi, 2011)
This research aims to study factors that can influence to future profit and cash flow on listed company from manufacture industry at Indonesian Stock Exchange in the year 2005-2007. This resesarch used profit, cash flow and cash dividend as independent variable. Type of this research is descriptive – verificative research.The object of this research is emiten from manufacture industry listed Indonesian Stock Exchange which publish income statement on December, 31, 2005 – 2007, obtaining profit on resesarch period and use rupiah in income statement. By using purposive sampling technique, there are 65 companies as resesarch object. The unstandardized multiple regression model is used to examine the influence of profit, cash flow and cash dividend toward future profit and cash flow both partial and simultaneously.The result of this resesarch show that (1) simultaneously, profit, cash flow, and cash dividend has strong positive influence toward future profit, (2) simultaneously, profit, cash flow, and cash dividend has positive influence toward future cash flow, (3)partialy, profit, cash flow, and cash dividend has positive influence toward future profit, but just profit and cash flow that has significant, (4) partialy, profit, cash flow hasn’t significant influence toward future cash flow, while cash dividen has positive significant influence toward future cash flow.